Contextualisation: A case study of a team within an international missional order - Kasebwe T.L. Kabongo (Verbum et Ecclesia, 2021)
Contextualisation is a process of seeking meaning and relevancy in a constantly changing world. It is a theological imperative if biblical values were to be relevant to everyone in the world. This research is a case study of InnerCHANGE South Africa (ICSA) efforts to be contextual. InnerCHANGE South Africa is part of an international missional order called InnerCHANGE, which was started in 1984 in the United States of America. International organisations face the danger of coming up with uniform principles and practices. Such uniformity is never innocent of cultural bias. It rendered their principles and practices relevant in some contexts and irrelevant in others. InnerCHANGE is an incarnational ministry that focuses on identification in communities of poverty. It described incarnational ministry as a model of Christ, a method, a message and a spiritual discipline. This study investigated how ICSA has been able to contextualise these four elements of incarnational ministry. It concluded that these contextualisation efforts are still work in progress. It pointed out the encouraging signs of seeing many local community members aligning themselves behind ICSA vision of seeing the gospel as the good news made visible. It finally pointed out the challenges of contextualisation it is still facing.